Teacher’s Reinforcements Affecting Students’ Willingness to Communicate (WTC): A Photovoice in EFL Classroom - Siti Jayanti Rahma; Bambang A. Loeneto; Soni Mirizon (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
In a globalization era, everything depends on technology. Technology has been developing in the role of teaching and learning process. This study aimed to find out: (1) the teachers’ perception of ICT use in their teaching and learning process; (2) to evaluate the progress of ICT integration program during the last five years at the school;(3) the problems faced by the teacher and students in using the ICT in the classroom; and (4) effects of using ICT in teaching and learning process. Twelve students and two teachers of English were chosen using purposive sampling as the respondents. Method of the study was descriptive qualitative research. The questionnaire, interview, observation, and documentation were used to collect the data. The results of the study showed that first, the teachers had positive attitude toward the use of ICT; second, the integration of ICT was found from the school’s facilities, the teachers’ participation in attending seminar and trainings, and the use of ICT for assignments in and outside the classrooms; third, the number of computers and a power blackout were the problems faced by both teachers and students; and fourth, from the questionnaires and interview, the teachers and students claimed that the ICT had great influence in teaching and learning process.